The Utilization of Student Worksheets on The Subject of Knowing Hindu, Budha, and Islamic Historical Legacy - Elce Purwandari; Agung Subakti; Hartatik Hartatik; Desy Seplyana; Jamilah Jamilah; Jamilah (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the use of Student Worksheets (LKS) as a social media learning medium for material knowing the historical heritage of Hinduism, Buddhism, and Islam in the fifth grade of Bingin Teluk State Elementary School (SDN). The method used in this research is a quantitative method in the form of a survey. The data collection technique was carried out using an online questionnaire in the form of a Google Form which was analyzed quantitatively descriptively. The data source is the fifth-grade students of SDN Bingin Teluk as many as 25 students. The results of the study revealed that students enjoy learning to use Student Worksheets, students regularly open or read Student Worksheets at home, Hindu, Buddhist, and Islamic materials are easy to understand using Student Worksheets, students are not lazy to read Student Worksheets when studying in class, students discuss together with friends. my seat. This research is new because it has never been done before at SDN Bingin Teluk. The contribution of research can provide understanding for other schools that want to use Student Worksheets as a learning medium, provide references for other researchers who want to conduct research related to the use of Student Worksheets as a learning medium that is used by students and teachers.